Remarks at the UN General Assembly High-Level Event on Financing for Development - Malpass, David (World Bank, Washington, DC, 2020)
World Bank Group President David Malpass provided an update on the World Bank’s development finance actions during this part of the pandemic. He spoke about the first goal in the Coronavirus (COVID-19) response was for the World Bank to take broad, fast action early and to provide large net positive flows to the world’s poorest countries. He mentioned that together with the IMF, and the World Bank Group (WBG) are making progress on debt transparency and relief. He described the IMF and WBG working to extend and broaden the debt moratorium and lay the foundations for debt reduction and would welcome the UN’s vocal support for full participation by all official bilateral creditors, including national policy banks. He also spoke about IMF and WBG working to expand fast-track Coronavirus (COVID-19) programs to include financing for the purchase and distribution of vaccines. He cautioned that the countries will also need to prepare for a different economy post-COVID, by allowing capital, labor, skills and innovation to move into new businesses and sectors. He concluded by saying that If we take action early with the large creative programs and sources of financing, we can help countries as the IMF Managing Director puts it, build forward a better and stronger, a greener, smarter and more equitable economy.